The Poetry of Place in the Literature of Mustafa Sadiq Al-Rafi’i (Book of the Poor as a Model) - Ramdani, Antar (Milev Journal of Research and Studies, 2021)
In this paper, we seek to investigate the features of poetry in the element of "place" used by Al-Rafe'ie in his book of "The Destitute" [In Arabic: Kitab Al-Masakin], specifically in the two stories: “The Fear of Ruin” and “The Pulverized Pearl”. In this regard, we highlighted the relationship between the element of "place" and the narration on one hand; and with the characters and time on the other hand. This is carried out to discover the features of poetry in his narration, the linguistic dimensions involved in it, and how Al-Rafe'ie dealt with the element of "place" and made use of it in these two stories in particular.